Comparing the blood oxygen level–dependent fluctuation power of benign and malignant musculoskeletal tumors using functional magnetic resonance imaging - Duan, Lisha; Huang, Huiyuan; Sun, Feng; Zhao, Zhenjiang; Wang, Mengjun; Xing, Mei; Zang, Yufeng; Xiu, Xiaofei; Wang, Meng; Yu, Hong; Cui, Jianling; Zhang, Han (Frontiers in Oncology, 2022)
Purpose: To compare the blood oxygen level-dependent (BOLD) fluctuation power in 96 frequency points range from 0Hz to 0.25Hz between benign and malignant musculoskeletal (MSK) tumors via power spectrum analyses using functional magnetic resonance imaging (fMRI). Materials and Methods: BOLD-fMRI and T1 weighted imaging (T1WI) of 92 patients with benign or malignant MSK tumors were acquired by 1.5 Tesla magnetic resonance scanner. For each patient, the tumor-related BOLD time series were extracted, and then the power spectrum of BOLD time series was calculated and was then divided into 96 frequency points. A two-sample t-test was used to assess whether there was a significant difference in the powers (the “power” is the square of the BOLD fluctuation amplitude with Arbitrary Unit) of each frequency point between benign and malignant MSK tumors. The ROC analysis was used to assess the diagnostic capability of distinguish between benign and malignant MSK tumors. Results: The result of the two-sample t-test showed that there was significant difference in the power between benign and malignant MSK tumor at frequency points 58 (0.1508Hz，P = 0.036), 59 (0.1534Hz，P = 0.032) and 95 (0.247Hz，P =0.014) respectively. The ROC analysis of mean power of three frequency points showed that the area of under curve is 0.706 (P=0.009), the cut off value is 0.73130. If the power of the tumor greater than or equal to 0.73130 is considered the possibility of benign tumor, the diagnostic sensitivity and specificity values are 83% and 59%, respectively. The post-hoc analysis showed that the merged power of 0.1508Hz and 0.1534 Hz in benign MSK tumors were significantly higher than malignant ones (P = 0.014). The ROC analysis showed that if the benign MSK tumor was diagnosed with the power greater than or equal to the cutoff value 1.41241, the sensitivity and specificity were 67% and 68%. Conclusion: The mean power of three frequency points at 0.1508Hz, 0.1534Hz and 0.247Hz may potentially be a biomarker to differentiate benign from malignant MSK tumors. By combining the power of 0.1508 Hz and 0.1534 Hz, we could better detect the difference between benign and malignant MSK tumors with higher specificity.